Oculoectodermal syndrome: twentieth described case with new manifestations - Daniela de Almeida Figueiras; Deborah Maria de Castro Barbosa Leal; Valter Kozmhinsky; Marina Coutinho Domingues Querino; Marina Genesia da Silva Regueira; Maria Gabriela de Morais Studart (Sociedade Brasileira de Dermatologia, 2016)
Abstract Oculoectodermal syndrome is a rare disease characterized by the association of aplasia cutis congenita, epibulbar dermoids, and other abnormalities. This report describes the twentieth case of the disease. We report a 4-year-old female child who presented with the classical features of the syndrome: aplasia cutis congenita and epibulbar dermoids. Our case expands the clinical spectrum of the disease to include: diffuse hyperpigmentation (some following the Blaschko´s lines); hypopigmented skin areas on the trunk; arachnoid cyst on the right fronto-parietal border; rounded left side of the hippocampus; and dermoid cyst underlying the bulb-medullary transition. Our patient also reported infantile hemangioma on the right wrist and verrucous hemangioma on the left leg, the latter not previously described in the literature.